Auranofin and its Analogues Show Potent Antimicrobial Activity against Multidrug‐Resistant Pathogens: Structure–Activity Relationships. (5th November 2018) - Marzo, Tiziano; Cirri, Damiano; Pollini, Simona; Prato, Marco; Fallani, Stefania; Cassetta, Maria Iris; Novelli, Andrea; Rossolini, Gian Maria; Messori, Luigi
Abstract: Due to the so‐called "antibiotic resistance crisis" new antibacterial agents are urgently sought to treat multidrug‐resistant pathogens. A group of gold‐ or silver‐based complexes, of general formula [M(PEt3 )X] (with M=Au or Ag, and X=Cl, Br or I), alongside with three complexes bearing a positive or negative charge—[Au(PEt3 )2 ]Cl, K[Au(CN)2 ] and [Ag(PEt3 )2 ]NO3 —were prepared and comparatively tested with auranofin on a representative panel of pathogens including Gram‐positive, Gram‐negative and Candida strains. Interestingly, all the gold and silver complexes tested were active on Gram‐positive strains, with the gold complexes having greater efficacy. The effects of the gold compounds were potentiated to a larger extent than silver compounds when tested in combination with a permeabilizing agent. A number of relevant structure–activity relationships emerged from the comparative analysis of the observed antibacterial profiles, shedding new light on the underlying molecular mechanisms of the action of these compounds. Abstract : Test your metal : The antimicrobial properties of a small group of metal complexes with general formula [M(PEt3 )X] (M=Au or Ag, X=Cl, Br or I) are measured and compared with three complexes bearing a positive or negative charge, that is, [Au(PEt3 )2 ]Cl, K[Au(CN)2 ] and [Ag(PEt3 )2 ]NO3 . The stability of complexes under the experimental conditions is shown to be a key parameter and a principal mechanism for resistance in Gram‐negative bacterial strains is reduced uptake. The results should aid the design of metal‐based antimicrobial agents.